Evaluation of dietary supplementation of garlic powder (Allium sativum) on the growth performance, carcass traits and meat quality of Japanese quails (Coturnix coturnix japonica) - Hassan Jalal; Sibel Canoğullari Doğan; Melania Giammarco; Damiano Cavallini; Lydia Lanzoni; Paolo Pezzi; Muhammad Zeeshan Akram; Isa Fusaro (Poultry Science)
ABSTRACT: Dietary supplementation with plant-based products may arise as part of an alternative strategy to using antibiotics as growth promoters in the poultry industry. Garlic powder (GP) possesses antimicrobial and antioxidant properties. The aim was to investigate the effect of dietary supplementation of GP on growth performance, carcass traits and meat quality of the Japanese quail. A total of 240, day-old mixed gender Japanese quail were assigned to 4 treatment groups, each group being replicated 4 times and containing 15 birds in each replication. Birds were provided with either a basal diet (control) or basal diet supplemented with 0.5%, 1% and 2% GP for 5 wk. At slaughter age, birds fed 1% GP had higher (P < 0.05) live weight and body weight gain when compared to the control. Supplementation with different levels of GP had no influence (P > 0.05) on feed intake, feed conversion ratio except 3rd wk, carcass traits and abdominal fat. Thiobarbituric acid, peroxide and pH values in breast meat of birds receiving GP (1% or 2%) after storage (0, 1, 3, 5, and 7 d) were lower (P < 0.05) than the birds in control. Furthermore, total psychrophilic bacteria count was lower in breast meat of birds supplemented with GP at any dose compared to the birds of control. Sensory characteristics such as color, aroma, juiciness and tenderness were observed significantly better (P < 0.05) in GP supplemented groups especially when fed 1% GP. In conclusion, supplementing the diet with 1% to 2% GP demonstrated growth-promoting effects and positively impacted meat quality, including sensory characteristics.